Topical ketoprofen TDS patch versus diclofenac gel: efficacy and tolerability in benign sport related soft-tissue injuries. Issue 3 (30th November 2006) - Esparza, Francisco; Cobián, César; Jiménez, José Fernando; García-Cota, Juan José; Sánchez, Carlos; Maestro, Antonio
Abstract : Objective: To compare the ketoprofen TDS patch with diclofenac gel in the treatment of traumatic acute pain in benign sport-related soft-tissue injuries. Design: 7–14 treatment days, prospective, randomised, open study. Patients: Outpatients aged 18–70 years diagnosed for painful benign sport-related soft-tissue injury (sprains, strains and contusions within the prior 48 h), randomised to either ketoprofen patch 100 mg once daily (n = 114) or diclofenac gel 2–4 g three times daily (n = 109). Intervention: 7–14 days of topical non-steroidal anti-inflammatory drugs treatment to assess the pain intensity changes (daily activities and spontaneous at rest) in a daily diary (100-mm Visual Analogue Scale (VAS)). Main outcome measurement: Pain intensity (VAS). Results: The ketoprofen patch was not inferior to diclofenac gel in reducing the baseline pain during daily activities (difference of –1.17 mm in favour of ketoprofen patch, 95% CI (–5.86 to 3.52), reducing to the baseline VAS 79%. Ketoprofen patch presented also a higher cure rate (64%) than diclofenac gel (46%) at day 7 (p = 0.004). Patient opinions about the treatment comfort (pharmaceutical shape, application and dosage) were also statistically higher for the ketoprofen patch (>80% of the patients rated as good or excellent the patch removal and skin adherence). Conclusion: Ketoprofen patches are effective and safe pain relievers for the treatment of sports injury pain with advantages compared with diclofenac gel.